STUDY OF PSYCHOLINGUISTIC PROPERTIES OF APHORISMS IN ENGLISH AND UZBEK LANGUAGE (The Conference Hub, 2025)
The aim of this study is to examine the psycholinguistic characteristics of aphorisms containing fear in English and Uzbek language. The article analyzes expressions and short phrases of fear from the point of view of language and psychology. Aphorisms in English and Uzbek differ in their meaning, structural aspects and linguistic features. Psycholinguistic analysis studies the influence of aphorisms about fear on the human psyche, psychological aspects of language and the transformative power of language. This study helps to identify the differences and similarities between the two languages.